Causal Relationships between Public Sector Agricultural Research Expenditures and Output - Pardey, Philip G.; Craig, Barbara J. (Wiley, 1989)
Allocative decisions concerning public sector agricultural research appear to be driven by both supply and politically mediated demand forces. In‐sample Granger tests, along with post‐sample predictive tests, suggest that simultaneity issues should not be ignored when modeling the research expenditure‐output relationship. The results also provide strong evidence that the impact of research expenditures on agricultural output may persist for as long as thirty years. These lags are substantially longer than those commonly used for agricultural research to date. The lagged effect of output on research appears to be shorter, though still between ten and twelve years.